Seroprevalence Of Classical Swine Fever In Karnataka - Shivaraj, D.B.; Patil, S.S.; Rathnamma, D.; Veeregowda, B.M.; Hemadri, D.; Geetha , S.; Reddy, G.B. Manjunatha; Sharada, R.; Shesharao; Rahman , H. (Indian Journal of Veterinary Sciences and Biotechnology, 2013)
A study was conducted to understand the current scenario of Classical swine fever (CSF) disease in Karnataka. Serum samples were collected from 517 pigs from 20 different districts of Karnataka and were tested for the presence of CSF antibodies. The prevalence of CSF antibodies from serum samples for the whole of Karnataka was 33% (173/517) in 20 districts. The southern Karnataka has the highest prevalence, which confirms the endemicity of the disease in that region and lowest prevalence in the northern Karnataka region. This is the first report that describes the seroepidemiology of CSF from Karnataka.